2013
DOI: 10.3892/or.2013.2752
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of the tumor-suppressor genes RASSF1A, GSTP1 and CDH1 in endometrial cancer

Abstract: Abstract. Endometrial cancer is a common gynecological malignancy with a good prognosis in early stages of the disease. The CpG island in the promoter region of tumorsuppressor genes are frequently methylated in various types of human cancers. In the present study, we examined the methylation status of the GSTP1, CDH1 and RASSF1A genes in endometrioid endometrial cancer (EEC), endometrial complex hyperplasia (EHP) and healthy endometrium with the aim to identify correlations between promoter hypermethylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Among the 24 TSGs studied, CDH13, RASSF1A, and GSTP1 were the most frequently methylated genes in endometrial hyperplasia and carcinoma. A recent study corroborated the findings of Nieminen et al, aberrant CpG methylation of the promoter region of GSTP1 and RASSF1A was found to be an important event in endometrial carcinogenesis and suggested to have an impact on tumor aggressiveness (Fiolka et al 2013).…”
Section: Role Of Epigenetic Modifications and Mirna Regulationsupporting
confidence: 82%
“…Among the 24 TSGs studied, CDH13, RASSF1A, and GSTP1 were the most frequently methylated genes in endometrial hyperplasia and carcinoma. A recent study corroborated the findings of Nieminen et al, aberrant CpG methylation of the promoter region of GSTP1 and RASSF1A was found to be an important event in endometrial carcinogenesis and suggested to have an impact on tumor aggressiveness (Fiolka et al 2013).…”
Section: Role Of Epigenetic Modifications and Mirna Regulationsupporting
confidence: 82%
“…Abnormalities in DNA methylation levels accompany early stages of endometrial carcinogenesis and may influence gene expression levels resulted in deregulation of apoptosis-associated genes (Tao and Freudenheim 2010;Ma and Gao 2014). Nowadays there are only a few scientific publications which have demonstrated DNA methylation status in apoptotic regulators during endometrial carcinogenesis and also during normal menstrual cycle (Zysman et al 2002;Salvesen et al 2004;Arafa et al 2008;Liao et al 2008;Pallares et al 2008;Fiolka et al 2013). In our study we investigated DNA methylation status of 22 apoptosisassociated genes in endometrial cancer tissue and healthy tissue using a commercially available methylation platform, EpiTect ® Methyl II Signature PCR Array (22) Kit (Qiagen).…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is major epigenetic modification in mammal, and changes in methylation patterns play a key role in tumor genesis with humans (Virmani et al, 2000;Dumitrescu et al, 2012;Fiolka et al, 2013). In particular, the promoter CpG island hypermethylation is closely related between inactivation and silencing, resulting in tumor suppressor loss of gene expression and X-chromosome inactivationmay, and affect development of carcinogenesis (Ki et al, 2008;Fiolka et al, 2013;Al-Temaimi et al, 2013). The aberrant promoter region methylation of tumor suppressor genes is associated with mechanism for carcinogenesis (Grote et al, 2006;Neyaz et al, 2008;Dumitrescu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%